2007
DOI: 10.1590/s0102-76382007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Índice de risco de mortalidade por endocardite infecciosa: um modelo logístico multivariado

Abstract: The higher the score, the higher the mortality rate. The mortality risk index may be used to estimate mortality in Infective Endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
(49 reference statements)
4
9
0
Order By: Relevance
“…The overall mortality rate in these patients was 18%, which was in agreement with other mortality rates reported between 13% and 40% [7], [17], [23], [34]. We obtained a low rate of postoperative complications (2.9%) during dental preparation.…”
Section: Discussionsupporting
confidence: 90%
“…The overall mortality rate in these patients was 18%, which was in agreement with other mortality rates reported between 13% and 40% [7], [17], [23], [34]. We obtained a low rate of postoperative complications (2.9%) during dental preparation.…”
Section: Discussionsupporting
confidence: 90%
“…The present study, consistently with a number of previous analyses [1215], showed that 2 out of the 6 most significant independent predictors of postoperative death in 440 endocarditis surgery patients were specific of the IE setting, that is, microbiology- or infection-related, and not included in the most commonly employed prognostic systems. …”
Section: Discussionsupporting
confidence: 89%
“…Until recently, only a small Brazilian study including 186 patients had tried to derive a score system from a mixed native and prosthetic endocarditis cohort [12]: single-center design and small numbers prevent direct wider applicability of that system, as well as ours. The aforementioned Duke's study by Gaca and colleagues, conversely, was based on more than 13,600 IE patients from the STS database [9]: the multicentric design and the large sample size provided optimal statistical strength and applicability at least over all North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al demonstrated that summation of clinical and echocardiographic scores as the predictors of mortality included: age over 40 years (4 points), New York Heart Association (NYHA) class-IV heart failure or cardiovascular shock (5 points), uncontrolled sepsis (6 points), conduction disorder (5 points), arrhythmia (8 points), a valve with extensive damage or abscess, or a prosthesis (5 points), large and mobile vegetation (4 points) [14]. Mortality rates for scores below 10 were 5.26% and for scores over 20 were and 78.9%.…”
Section: Discussionmentioning
confidence: 99%